Testing a model of global citizenship in higher education institutions in the SADC region - Wagener, E.; Smith, M.; Frantz, J. (South African Journal of Higher Education, 2023)
Higher Education Institutions (HEIs) equip the labour force with the necessary skills and knowledge to engage effectively as global citizens. The aim of this study was to test the Reysen and Katzarska-Miller (2013) model of global citizenship identity in the context of HEIs in the SADC region. This study approaches global citizenship from a social identity perspective in which identification as a global citizen is at the center. Identification as a global citizen is theorised to follow a Normative Environment and Global Awareness as antecedents. In turn global citizen identification (GCI) produces six prosocial outcomes. This model proposes nine domains of Global Citizenship including two antecedents, an identification as a global citizen and six prosocial outcomes. Participants included 242 students and staff from universities across seven countries participating in the UNESCO #OpenUpYourThinking Researchers Challenge. Participants completed an online version of the Global Citizenship Scale. In this study, the antecedents and outcomes of GC were all positively and significantly correlated demonstrating a linear relationship between all domains. The results provided empirical support for this model in the context of HEIs in the SADC region. GCI was significantly predicted by normative environment and global awareness. In turn, GCI significantly predicted the six prosocial outcomes. Indirect prediction effects between normative environment, global awareness and GCI significantly predicted the six prosocial outcomes.